Complexity in behavioural organization and strongylid infection among wild chimpanzees. (July 2017) - Burgunder, J.; Pafčo, B.; Petrželková, K.J.; Modrý, D.; Hashimoto, C.; MacIntosh, A.J.J.
Abstract : Objectively measuring the effects of parasitism on animal health is challenging, especially in the wild. Analyses of behavioural organization are increasingly used for this purpose, to identify animals in pathological or otherwise challenged states. Here, we investigated the possible impact of gastrointestinal helminth infection on the behaviour of wild chimpanzees, Pan troglodytes schweinfurthii, by applying fractal analysis to their feeding patterns. We predicted that higher intensity of strongylid infection should be associated with altered organizational complexity in temporal sequences of behaviour. We observed 15 habituated male chimpanzees in Kalinzu Reserve Forest, Uganda, and collected behavioural time series via focal animal sampling. We quantified the number of strongylid eggs per gram of faecal sediment using a modified simple sedimentation method to estimate the intensity of infection with strongylid nematodes. We used detrended fluctuation analysis (DFA) to explore long-range dependence in binary sequences of feeding behaviour as an index of organizational complexity along a stochastic-deterministic gradient. We then built several generalized linear mixed models to examine the relationship between behavioural organization and strongylid infection. Our results indicate that chimpanzee feeding sequences are long-range dependent and antipersistent, i.e. short bouts tended to be followed by long bouts and vice versa. Furthermore, the complexity of chimpanzee feeding sequences and the intensity of infection with strongylid nematodes were positively related: individuals with more intense infections exhibited more stochastic feeding sequences. In contrast, more conventional analyses did not reveal any relationship between parasitism and chimpanzee behaviour, nor did a survival analysis find variation in the probability of switching between behaviour states across chimpanzees with varying infection phenotypes. This work suggests that strongylid nematodes do pose a challenge for wild chimpanzees, manifest as altered organizational complexity in behaviour sequences, and provides further evidence that fractal analyses can have a valuable role in animal health monitoring. Highlights: We investigated complexity loss in relation to intestinal parasites in chimpanzees. Fractal analysis revealed behavioural alterations with strongylid infection. Fluctuations in feeding sequences are long-range correlated and antipersistent. More heavily parasitized chimpanzees had more stochastic feeding sequences. Probability of switching behaviour was not affected by intensity of infection.